LEGAL RESPONSIBILITY FOR COPYRIGHT INFRINGEMENT IN THE SALE AND PURCHASE OF UNOFFICIAL K-POP MERCHANDISE AS REVIEWED FROM MUI FATWA NO. 1 2005 - Nurhaliza, Fitria; Hasanah, Uswatun (Program Pascasarjana UIN Sumatera Utara, 2026)
K-Pop merchandise is part of the work protected by intellectual property rights (IPR), both in the form of copyright and trademark rights. However, the practice of buying and selling unofficial K-Pop merchandise is still rampant, especially through online marketplace platforms, and raises legal and ethical issues. This study aims to analyze the forms of copyright infringement in the sale of unofficial K-Pop merchandise and the legal liability of the parties involved, reviewed from positive law and the MUI Fatwa Number 1 of 2005. This study uses an empirical juridical approach with data collection techniques through online observation of the practice of selling unofficial merchandise on the Shopee marketplace as well as a literature study of laws and Islamic legal literature. The results show that the practice of selling unofficial K-Pop merchandise contains copyright and trademark violations due to the use of works without permission for commercial purposes, thus contradicting the provisions of the Copyright Law and the principles of Islamic muamalah. The novelty of this study lies in the integrative analysis of the legal liability of sellers and marketplaces as transaction facilitators, which is not only juridical, but also includes moral and religious dimensions. This study confirms that this practice is not justified under either positive law or Islamic law because it violates the principles of justice and protection of property rights.